Lost in evolution : - Kawabata, Hiroto (Japan Publishing Industry Foundation for Culture (JPIC), 2020)
This book grew out of an effort to gain a better understanding of the peoples who populated Asia in ancient times and to present these findings from a modern Homo sapiens perspective.